Guided Endodontics, Static Guides Development, Design, and Clinical Applications - David W. Kelliny (Taylor & Francis Group, 2023)
ABSTRACTBackground In the last 7-8 years, Guided Endodontics has garnered attention in articles and lectures, yet a substantial gap persists in elucidating the creation and 3D printing of an Endo Guide. The intricacies of design software and 3D printing have confounded many, compelling speakers, and researchers to rely on third-party labs. Consequently, the potential of Endodontic Access guides is hindered by a lack of guidance on design and fabrication, impeding their widespread adoption, especially in challenging cases. The author envisions greater awareness and utilization of this method to enhance endodontic treatment outcomes, emphasizing simplicity in procedures.Types Articles reviewed were published in many different journals, mostly all of them are case presentations, few discuss the concept and others not at all. This deficiency in current literature led to this publication hoping to simplify the technique and explain the process.Results The accuracy of Guided Endodontic has been tested repeatedly and presented consistent results, the accuracy of such guides and ease of use from a novice operator to an expert, could not be more discernible.Practical implications Integration of Endodontic Access Guides and 3D printing holds potential for widespread use in endodontic practices, residencies, dental schools, and general dentistry. This integration facilitates training for new dentists in 3D printing and endodontic case management. Endodontists benefit from enhanced accuracy and predictability in treating challenging cases, while general practitioners can avoid mishaps like perforations and instrument separations, improving overall endodontic treatment outcomes across different dental settings.